Testing theories of job creation: does supply create its own demand? - Mikael Carlsson; Stefan Eriksson; Nils Gottfries (Institute for the Study of Labor (IZA), 2006)
How well do alternative labor market theories explain variations in net job creation? According to search-matching theory, job creation in a firm should depend on the availability of workers (unemployment) and on the number of job openings in other firms (congestion). According to efficiency wage and bargaining theory, wages are set above the market clearing level and employment is determined by labor demand. To compare models, we estimate an encompassing equation for net job creation on firm-level data. The results support demand-oriented theories of job creation, whereas we find no evidence in favor of the search-matching theory.
Keywords: E24; J23; J64; 330; job creation; involuntary unemployment; search-matching; labor demand; Beschäftigungspolitik; Arbeitsmarkttheorie; Arbeitsnachfrage; Arbeitsplatzsuchmodell; Arbeitslosigkeit; Lohn